Participation of local service providers in systemic market approaches in the dairy sector of Rangpur district - Mojumdar, Ashish Kumar; Rahman, Md Anisur; Goswami, Pallab; Huda, Saiful (Research in Agriculture Livestock and Fisheries, 2021)
The main purpose of the study was to determine the participation of Local Service Providers (LSPs) in systemic market approaches (SMA) in dairy sectors in two Upazilla Pirgacha and Badargonj under Rangpur district. Ninety-nine (99) LSPs were randomly selected as sample from an updated list of 495 LSPs. A pretested and structured interview schedule was used to collect data from the respondents during 16 August to 17 September 2018. Simple and direct questions with different appropriate scales were used to obtain information. Descriptive statistics, correlation, and multiple regression analysis were used. The top-ranked activities regarding the participation of LSPs was referral linkage with DLS for the critical or serious condition of livestock treatment, linkage with dairy producers’ group to assess the demand of information, develop collection point’s adjacent place of the community. Slightly above four-fifths (84.8 percent) of the respondent had high participation in systemic market approaches. Correlation analysis indicated that among seven selected characteristics of the respondent’s annual income, cosmopoliteness, training received, innovativeness, and extension media contact of the respondents had significant positive relationship with their participation in SMA, however, age and family size had no significant positive relationship. Regression analysis indicated that cosmopoliteness, training received, innovativeness, and extension media contact of the respondents had a positive contribution with their participation in SMA. The top-ranked problem (1st) faced by the LSPs was ‘legal permission from Government authority and apparently, the lowest proportion of LSP faced problems on ‘Lack of vehicle service for their movement’ service on dairy subsectors. Res. Agric., Livest. Fish.8(2): 211-221, August 2021